Answer:
8cm
Step-by-step explanation:
2 cm =1 ft so if i multiply it by 4ft, and remember 2 cm =1 ft so 2×4=8
8cm
Answer:
877.1929824561 dollars
Step-by-step explanation:
100000÷114= 877.1929824561 dollars
hope it helps!
![\boxed{(x - a)(x - b) = 0}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%28x%20-%20a%29%28x%20-%20b%29%20%3D%200%7D)
The equation above is the intercept form. Both a-term and b-term are the roots of equation.
![x = - \frac{1}{3} \\ x = 5](https://tex.z-dn.net/?f=x%20%3D%20%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%5C%5C%20x%20%3D%205)
These are the roots of equation. Therefore we substitute a = - 1/3 and b = 5 in the equation.
![(x + \frac{1}{3} )(x - 5) = 0](https://tex.z-dn.net/?f=%28x%20%2B%20%20%5Cfrac%7B1%7D%7B3%7D%20%29%28x%20-%20%205%29%20%3D%200)
Here we can convert the expression x+1/3 to this.
![x + \frac{1}{3} = 0 \\ 3x + 1 = 0](https://tex.z-dn.net/?f=x%20%2B%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%3D%200%20%5C%5C%20%203x%20%2B%201%20%3D%200)
Rewrite the equation.
![(3x + 1)(x - 5) = 0](https://tex.z-dn.net/?f=%283x%20%2B%201%29%28x%20-%205%29%20%3D%200)
Simplify by multiplying both expressions.
![3 {x}^{2} - 15x + x - 5 = 0 \\ 3 {x}^{2} - 14x - 5 = 0](https://tex.z-dn.net/?f=3%20%7Bx%7D%5E%7B2%7D%20%20-%2015x%20%2B%20x%20-%205%20%3D%200%20%5C%5C%203%20%7Bx%7D%5E%7B2%7D%20%20-%2014x%20%20-%205%20%3D%200)
<u>Answer</u><u> </u><u>Check</u>
Substitute the given roots in the equation.
![3 {(5)}^{2} - 14(5) - 5 = 0 \\ 75 - 70 - 5 = 0 \\ 75 - 75 = 0 \\ 0 = 0](https://tex.z-dn.net/?f=3%20%7B%285%29%7D%5E%7B2%7D%20%20-%2014%285%29%20%20-%205%20%3D%200%20%5C%5C%2075%20-%2070%20-%205%20%3D%200%20%5C%5C%2075%20-%2075%20%3D%200%20%5C%5C%200%20%3D%200)
![3( - \frac{1}{3} )^{2} - 14( - \frac{1}{3}) - 5 = 0 \\ 3( \frac{1}{9} ) + \frac{14}{3} - 5 = 0 \\ \frac{1}{3} + \frac{14}{3} - \frac{15}{3} = 0 \\ \frac{15}{3} - \frac{15}{3} = 0 \\ 0 = 0](https://tex.z-dn.net/?f=3%28%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20%29%5E%7B2%7D%20%20-%2014%28%20-%20%20%5Cfrac%7B1%7D%7B3%7D%29%20-%205%20%3D%200%20%5C%5C%203%28%20%5Cfrac%7B1%7D%7B9%7D%20%29%20%2B%20%20%5Cfrac%7B14%7D%7B3%7D%20%20-%205%20%3D%200%20%5C%5C%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%2B%20%20%5Cfrac%7B14%7D%7B3%7D%20%20-%20%20%5Cfrac%7B15%7D%7B3%7D%20%20%3D%200%20%5C%5C%20%20%5Cfrac%7B15%7D%7B3%7D%20%20-%20%20%5Cfrac%7B15%7D%7B3%7D%20%20%3D%200%20%5C%5C%200%20%3D%200)
The equation is true for both roots.
<u>Answer</u>
![\large \boxed {3 {x}^{2} - 14x - 5 = 0}](https://tex.z-dn.net/?f=%20%5Clarge%20%5Cboxed%20%7B3%20%7Bx%7D%5E%7B2%7D%20%20-%2014x%20-%205%20%3D%200%7D)
F^-1(x)= x/9 + 1/3
To find this, just interchange the variables and solve for y.
y=9x-3
x=9y-3
x+3=9y
divide by nine
Step-by-step explanation:
snznwjma.nzjshzbsnznkakj to see you soon and inbox